Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1128/jvi.06000-11
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral Therapy Reduces the Magnitude and T Cell Receptor Repertoire Diversity of HIV-Specific T Cell Responses without Changing T Cell Clonotype Dominance

Abstract: After initiation of antiretroviral therapy (ART), HIV loads and frequencies of HIV epitope-specific immune responses decrease.A diverse virus-specific T cell receptor (TCR) repertoire allows the host to respond to viral epitope diversity, but the effect of antigen reduction as a result of ART on the TCR repertoire of epitope-specific CD8 ؉ T cell populations has not been well defined. We determined the TCR repertoires of 14 HIV-specific CD8 ؉ T cell responses from 8 HIV-positive individuals before and after in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 57 publications
0
34
1
Order By: Relevance
“…In this study, we did detect increased autologous nAb titers, but this was independent of bnAb treatment and most likely a function of extended viral exposure in these chronically infected animals. In contrast, SHIV-specific CD8 ϩ T-cell frequencies significantly declined in animals that had received bnAbs, most likely due to memory cell contraction in the setting of reduced antigen, as has been described for patients on antiretroviral therapy (ART) (36). It should be noted that the duration of antibody therapy in this model is brief, due to the potential for cross-species immune responses to the passively administered antibody.…”
Section: Discussionmentioning
confidence: 71%
“…In this study, we did detect increased autologous nAb titers, but this was independent of bnAb treatment and most likely a function of extended viral exposure in these chronically infected animals. In contrast, SHIV-specific CD8 ϩ T-cell frequencies significantly declined in animals that had received bnAbs, most likely due to memory cell contraction in the setting of reduced antigen, as has been described for patients on antiretroviral therapy (ART) (36). It should be noted that the duration of antibody therapy in this model is brief, due to the potential for cross-species immune responses to the passively administered antibody.…”
Section: Discussionmentioning
confidence: 71%
“…This exhausted state is associated with the upregulation of multiple activation and coinhibitory molecules (see below) (49)(50)(51)(52)(53)(54)(55). Several studies have demonstrated that prolonged ARV therapy results in some restoration of polyfunctionality and at least partial downregulation of activation and exhaustion markers (49)(50)(51)(52)(56)(57)(58)(59)(60). It is tempting to speculate that, despite being reduced in numbers, the HIV-specific CD8 + T cells that remain in ARV-treated subjects may be more functional, less restrained by coinhibition, and less proapoptotic.…”
Section: + T Cell-mediated Eradicationmentioning
confidence: 99%
“…With declining levels of plasma viremia and subsequent suppression, levels of Gag-specific and Pol-specific CTL precursors decrease and these correlate with decreased CD8 + IFNγ responses [62]. Not only is there a decrease in the frequency of epitope-specific T cells, but also in the number of T cell clonotypes within epitope-specific T cell repertoires [63]. With declining plasma viremia on ART, CD4 + T cell frequencies increase in blood and gut mucosal tissue within the first 9 months after starting ART [64 ▪ ].…”
Section: Hiv-specific Responses During Antiretroviral Therapymentioning
confidence: 99%